Dynamic interactions among knowledge management, strategic foresight and emerging technologies. Issue 2 (11th November 2020) - Nascimento, Leandro da Silva; Reichert, Fernanda Maciel; Janissek-Muniz, Raquel; Zawislak, Paulo Antônio
Abstract : Purpose: This paper aims to discuss the dynamic interactions among knowledge management, strategic foresight and emerging technologies, resulting in a framework that can help companies to shape these interactions for achieving positive outcomes. Design/methodology/approach: This conceptual paper is based on prior literature streams, which were interrelated through an abductive research process. This iterative conceptualization approach led to the formation of testable propositions that advance the understanding on the interactions among knowledge management, strategic foresight and emerging technologies. Findings: The framework demonstrates the existence of an actions cycle between strategic foresight and knowledge management through a constructivist perspective, where one can improve the other. These interactions can be useful both for the development of emerging technologies and for identifying these innovations in market that can be applied in companies. Hence, all these dynamic interactions do not point to a hegemonic relationship of one construct over the others, but for the value equality among them. Originality/value: Although current literature points to the existence of relationships among knowledge management, strategic foresight and emerging technologies, the dynamism inherent in these interactions as well as their positive effects for companies' results are not properly discussed. This paper fills such a gap and proposes directions for future research.